Variasi Ikonografi Arca-Arca Perwujudan Perunggu Koleksi Museum Bali Dan BPCB Bali-Nusa Tenggara - Pradnyana Adi Putra, Putu; Redig, I Wayan; Aryana, A. A. Gde (Humanis, 2018)
The so called ‘’Dead Portrait’’ statues are kind of archaeological remains from the Hindu-Buddhist period that is very much encountered in Bali. So far the sculptures of the much-studied are the statues made from stones, while the bronze statues are still very little known. This study examines the iconographical variation and its causal factors on the so-called bronze dead portrait statues collection of Bali Museum and BPCB Bali-Nusa Tenggara. The author uses data collection methods such as observation, interview and literature study and data processing methods through the analysis of iconography, iconometry, iconoplastic, and iconology. The theory used to refine the interpretation of the results of the analysis is the Theory of Iconography and Iconology of Erwin Panofsky. Based on the research results found that there are variations of iconography among the bronze dead portrait collection of Bali Museum and BPCB Bali-Nusa Tenggara. The iconographic variations can be seen in the variety of jewelry, dress, body, and body postures. The iconography variation itself is caused by the ability and creativity of artists, social factors, and religious factors and beliefs.